EFEKTIVITAS TERAPI MUSIK KLASIK LULLABY TERHADAP PENURUNAN KECEMASAN IBU BERSALIN KALA I DI RUANGAN VK RSUD PROF. W. Z. JOHANNES KUPANG - Maria O. Betan; Yuliana Dafroyati; Piga D. Rihi; Yosephalina Rindya Nahak Bria (Bajang Institute, 2026)
Anxiety during the first stage of labor is a common psychological condition that can negatively affect the progress of labor, maternal well-being, and fetal condition. Unmanaged anxiety may increase stress responses, delay cervical dilatation, and reduce maternal comfort during childbirth. One non-pharmacological intervention that can be applied is classical lullaby music therapy, which has relaxing and calming effects. This study aimed to determine the effectiveness of classical lullaby music therapy in reducing anxiety levels among first-stage laboring mothers in the delivery room of Prof. W. Z. Johannes Regional General Hospital, Kupang. This study employed a nursing innovation project using a pre–post intervention approach. Anxiety levels were measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS). The intervention consisted of administering classical lullaby music therapy during the first stage of labor in a supportive environment. The results showed a reduction in anxiety levels among laboring mothers after the administration of classical lullaby music therapy, as indicated by decreased anxiety scores and reduced anxiety symptoms. In conclusion, classical lullaby music therapy is effective as a non-pharmacological intervention in reducing anxiety among first-stage laboring mothers and can be recommended as part of maternity nursing care.